DEVELOPMENT WORKERS AS KNOWLEDGE WORKERS – A STUDY OF FINNISH DEVELOPMENT WORKERS IN NAMIBIA - Manyando, Maaria (My University, 2017)
In the 21st century poverty still remains a pressing matter for the majority of the human population. However, as development is not anymore measured only by monetary wealth communities are evaluated by measures of social conditions and humanitarian wellbeing, as well as, their abilities to create, share and use knowledge. As development organisations tackle several challenges in the development sector, organisational efficiency has become a key tool for achieving more successful development interventions. As the business sector has identified knowledge management (KM) as a key to competitive advantage the development sector is also seeking to enforce their interventions through KM. This thesis addresses the needs of KM in the development sector from the viewpoint of the business sector; especially looking at knowledge stickiness that was originally described by Szulanski in relation to intrafirm knowledge transfers. This explorative study examines knowledge transfers between Finland and Namibia from the viewpoint of knowledge workers. Qualitative methods were used to analyze the data collected through semi-‐‑structural interviews. The theory of knowledge stickiness was found to be useful in investigating knowledge transfer in the development sector. However, knowledge transfer alone was found to be insufficient in addressing the inadequacies in KM in the development sector. Furthermore, it was found that situated learning complements knowledge transfer in addressing the specific needs discovered in the literature review and empirical data.
Keywords: Knowledge Transfers; Knowledge Stickiness; Development Sector; Situated Learning; Namibia; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|